Mapping Nonsquare and Unevenly Spaced 2-D SLDV Data of an Aircraft Fuselage by Using Spatial DFT-IDFT Techniques - William Xinzuo Li; Larry D. Mitchell; Min-Fu Lu; Michael L. Neumann (Shock and Vibration)
The scanning laser Doppler vibrometry (SLDV) technique provides velocities of a structure at 2-dimensional (2-D) angularly evenly spaced (in the laser scanning sense) data points. This causes an unevenly spaced data point distribution on the surface of the test structure. In many cases evenly spaced data point distribution with square or rectangular grids is highly desirable. In this study the SLDV velocity data of a partial surface area of an aircraft fuselage were mapped to truly spatial evenly spaced coordinates by using the spatial DFT-IDFT technique with minimum distortion. This 2-D data mapping technique certainly is not limited to the fuselage, hut can he very useful for many other 3-D structures.